The Physical Touch of The Rasulullah saw to Aisyah bint Abū Bakr r.a. In The Light of The Hadith - Varendy, Mochamad; Ilmiyah​, Dakhirotul (STAIN Majene, 2024)
This study aims to determine the forms of physical touch carried out by Rasulullah ﷺ towards Aisyah bint Abu Bakar r.a, while fasting. The research method is literature study, the data sources obtained come from articles, books, and other readings. The result of the analysis in this study is that the physical touch carried out by the Messenger of Allah in the form of kissing aisyah r.a in a state of fasting according to the oendaoat of imam shafi'i is permissible, because the apostle of Allah once did it, but it becomes makruh for someone who cannot hold his lust, in the hadith narrated by aisyah r.a when it happened she smiled because she felt the tenderness and romance carried out by the Rasulullah.